2021
DOI: 10.7759/cureus.15790
|View full text |Cite
|
Sign up to set email alerts
|

Factors and Determinants of Choosing Pathology as a Future Career: Results From a Multi-Institution Study

Abstract: BackgroundGlobally, less than 10% of graduating medical students select pathology as a future career. Many factors were reported from different settings to influence the choice of pathology. The aim of this study was to investigate the factors that determine medical students' preferences in choosing pathology as a future career. MethodsThis cross-sectional study surveyed students from three governmental medical schools in Riyadh, Saudi Arabia. A self-administered questionnaire that contained demographic questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A multi-institution investigation found just 5% of undergraduates declare pathology as their first choice in the future. 12 An online investigation provided that the percentage of undergraduate medical students who chose pathology as their first choice for a future residency program was only 0.7, even though 8.7% of them thought about it. 10 Comparing the findings of our investigation to similar international studies yielded several similarities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A multi-institution investigation found just 5% of undergraduates declare pathology as their first choice in the future. 12 An online investigation provided that the percentage of undergraduate medical students who chose pathology as their first choice for a future residency program was only 0.7, even though 8.7% of them thought about it. 10 Comparing the findings of our investigation to similar international studies yielded several similarities.…”
Section: Discussionmentioning
confidence: 99%
“…The study questionnaire contains 20 questions and based on similar studies conducted previously. [9][10][11][12][13][14] The face validity of the instrument was assessed, and the instrument was reviewed by two pathologists. The developed questionnaire based on three major components.…”
Section: Methods Of Data Collection Study Tool and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of engagement results in limited comprehension of pathologists' roles, impact on patient management, lifestyle, and other pertinent considerations for career selection. Consequently, many students overlook pathology as a prospective field for their future endeavors [10]. International statistics have revealed that merely 1%-3% of medical school graduates from countries such as Australia, Canada, the United States, and the United Kingdom opt for a career in pathology [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…International statistics have revealed that merely 1%-3% of medical school graduates from countries such as Australia, Canada, the United States, and the United Kingdom opt for a career in pathology [11][12][13][14]. In Saudi Arabia, studies conducted in Dammam and Riyadh have underscored similar trends, where only a minute fraction of medical students, ranging from 1.1% to 5%, express interest in pursuing pathology [10,15].…”
Section: Introductionmentioning
confidence: 99%